Hypergravity as a Possible Way of Bone Tissue Engineering in Osteoblastic Differentiation from Mesenchymal Stem Cells: A Systematic Review - Sudrajad, Wisnu; Indrawan, Andre Erica; Kusuma, Devangga; Soetojo, Bagus Wibowo; Suroto, Heri ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: Tissue engineering development has become a highlight in recent decades. One of the key areas of focus is producing mature bone tissue to overcome orthopedic problems, such as bone defects. Various cultures have been implemented on stem cells; some induce osteoblastic differentiation markers, while others have the opposite effect. Microgravity has been proven in several studies to inhibit the expression of osteogenic differentiation markers. Conversely, hypergravity is expected to have the opposite impact, supporting stem cells in the osteogenesis pathway. Methods: A literature search was conducted using online databases including Sciencedirect, PubMed, and Proquest, covering the period from 2008 to 2022. This search considered only experimental studies published in English. The keywords used in this research were "hypergravity" and "mesenchymal stem cell." All acquired data were processed and analyzed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines (2020). Results: Initially, 190 studies were collected from online databases based on relevant keywords. After screening, 5 studies were included in the final analysis, focusing on hypergravity treatment and its effects on mesenchymal stem cells (MSCs). Conclusion: Hypergravity shows a significant and strong impact on osteoblastic differentiation. This study revealed that a gravity force of 30G and a culture duration of 7 to 14 days are the most optimal combination for inducing osteoblastic differentiation in MSCs.